PERAWATAN MESIN CUTTING RETURN BENDS - Gunawan, Hendi; Puspawan, Angky; Helmizar (UNIB Press, 2023)
The cutting return bend machine itself adopts a programmable logic controller for the interface control center between man and machine for its operation. With the characteristics of high-level optimization, speed, comfortable operation, high precision, reliable performance and attractive appearance. For the use of the cutting return bend machine itself, which is used for the production of u-shaped tubes which will later be used for the manufacture of evaporators and condensors. Maintenance also includes all necessary actions to be able to maintain and maintain product quality so that there is no damage or disruption to the machine so that producing products can achieve the targets as desired by the company. From the observations made, it is found that the problems that occur in the cutting return bend machine at PT. Panasonic Manufacturing Indonesia are damage to the mandrell, stripper,and problem with the bending mechanism. The solution of these problems are need to maintenance of the machine, which is corrective maintenance, preventive maintenance, predictive maintenance, and even emergency maintenance.